Extra resources for TROPAG abstracts - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Three European organizations have collaborated in the production of the latest collection of Abstracts on Tropical Agriculture (TROPAG). These monthly Abstracts have long been published by the Dutch organization Koninklijk Instituut voor de Tropen...